1988
DOI: 10.1266/jjg.63.43
|View full text |Cite
|
Sign up to set email alerts
|

Alternative smooth or stepped altitudinal cline of fecundity in Drosophila teissieri and D. yakuba in the Ivory Coast.

Abstract: Drosophilateissieri and D. yakuba are two closely related species within the melanogaster species subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Female M. roeselii had higher levels of polyandry at higher latitudes, a pattern contrary to that seen in another nuptial-gift-giving insect, the green-veined white butterfly (Välimäki and Kaitala 2006, 2010; but see Devaux and Lachaise 1987). The pattern in our study could not be explained as an artifact of sampling date, because the bush-crickets were sampled from north to south; thus, those from northern latitudes were at an earlier stage of their mating season (some undeveloped nymphs still occurred at the time of collection in the north).…”
Section: Discussioncontrasting
confidence: 65%
“…Female M. roeselii had higher levels of polyandry at higher latitudes, a pattern contrary to that seen in another nuptial-gift-giving insect, the green-veined white butterfly (Välimäki and Kaitala 2006, 2010; but see Devaux and Lachaise 1987). The pattern in our study could not be explained as an artifact of sampling date, because the bush-crickets were sampled from north to south; thus, those from northern latitudes were at an earlier stage of their mating season (some undeveloped nymphs still occurred at the time of collection in the north).…”
Section: Discussioncontrasting
confidence: 65%
“…Crosses between allopatric populations from high and low elevation, produce flies of intermediate fecundity, suggesting a genetic component to fecundity. Interestingly, a congeneric species, D. yakuba, displays rising fecundity with increasing altitude in a stepwise manner, perhaps linked to abrupt changes in the availability of particular habitat types (Devaux & Lachaise, 1987).…”
Section: (7 ) Fecunditymentioning
confidence: 99%
“…Depending on geographical region, population or species, some studies have found that altitudinal clines exhibit opposite directionality (starvation resistance in D. buzzatii : Sørensen et al ., vs. Sarup & Loeschcke, ; fecundity in D. yakuba vs. D. teissieri : Devaux & Lachaise, ). Others have failed to find clear altitudinal clines altogether: Bubliy & Loeschcke () measured eight traits across an elevational transect in D. buzzatii and D. simulans but did not find clinality.…”
Section: Introductionmentioning
confidence: 99%